Crowding Out of Informal Economy Labour Supply by Unconditional Child Benefits - Janusz Jabłonowski (Gospodarka Narodowa. The Polish Journal of Economics, 2022)
The article proposes a modified version of a theoretical model that crowds out less educated workforce from the informal economy in response to a shock in government transfers. The negative impact of universal child benefits (UCB) is measured by the outflow of labour from the informal economy in Poland. After it was introduced in the country in 2016, the “Family 500+” child benefit programme probably caused a permanent outflow of some 160,000 jobs from the labour market. The study verifies this assumption with a real business cycle (RBC) model, with two types of households responding to a positive shock resulting from government transfers. The endogenous growth factor in the model results from the rate of return on higher education and lifelong learning. The model describes the statistical aggregates of the Polish economy. A Bayesian estimation shows an acceptable fit to the time series, which allows for wider use of the fiscal impulse resulting in a decline in the economic activity of beneficiaries. The study adds to a debate on the margins of government intervention in the economy, which at some point may displace less educated workers in the shadow economy.